IDENTIFYING HOW NOVICE RESEARCHERS SEARCH, LOCATE, CHOOSE AND USE WEB RESOURCES AT THE EARLY STAGE OF RESEARCH - Ismail, Maizatul Akmar; Abdul Kareem, Sameem (Malaysian Journal of Library and Information Science, 2017)
This paper describes the process of identifying novice researchers’ information needs. The study sampled postgraduate students at the Faculty of Computer Science and Information Technology, University of Malaya, Malaysia. The study utilized three types of data gathering techniques: (a) observations to gauge further understanding the novice researchers’ information seeking behaviour while searching for research related sources on the Web; (b) a questionnaire-based survey to identify the artifact or the resources they use for the research activities; and (c) interviews with expert researchers to gauge further information needs of novice researchers. Results indicate that novice researchers rely on thesis, e-book, journals and conference proceedings as major scholarly resources. The facilitation of searching for research information on the Web is poorly supported by existing search engines. As such, the information seeking behaviour of novice researchers needs to be supported by specific research tools. Five important research information that novice researchers need to be acquainted with are: related literature, centre of research excellence, research trend, experts in specific research area and the specific databases and online resources. The paper put forward features of an institutional repository system that would support novice researchers’ scholarly activities based on their research information needs.